Modelowanie rozwoju gospodarczego na podstawie rozszerzonego modelu wzrostu Solowa-Swana z uwzgl\~nednieniem aspektu przestrzennego; The modeling of the economic development on the basis of an extended Solow-Swan growth model with the inclusion of spatial aspect - Beata Bal-Domanska; Michal Bernard Pietrzak (Institute of Economic Research (IER), 2014)
– The objective of the article is to identify and evaluate spatial relations in terms of economic determinants for the regions of Central and Eastern European countries (in accordance with Eurostat methodology NUTS-2 stands for the corresponding level) having applied the construction of an augmented, neoclassical Mankiw-Romer-Weil growth model. The study covered the period of three years: 2000, 2005 and 2010. The obtained results confirmed the significance of spatial relations, in the evaluation of relations combining growth factors, for the level of economic growth. The statistically significant impact, however, was observed only in case of the factor illustrating human capital.
Keywords: C21; O11; R11; 330; augmented Mankiw-Romer-Weil growth model; spatial econometrics; Central and Eastern European regions